Examining terror management theory in Ukraine: impact of air-raid alarms and explosions on mental health, somatic symptoms, and well-being - Stieger, Stefan; Lewetz, David; Paschenko, Svitlana; Kurapov, Anton (Frontiers in Psychiatry, 2023)
Objective: This study sought to evaluate Terror Management Theory (TMT) assumptions about death awareness and its psychological impact in the context of a real-world war situation with high external validity. We examined if factors such as habituation to war circumstances and psychological resilience could buffer the effects on civilians' anxiety, physical and mental health, and affect. Method: We implemented a pre-registered smartphone-based experience sampling method study over four weeks, with 307 participants (k = 7,824) living in war-affected areas in Ukraine whereby participants were regularly exposed to war situations, including air-raid alarms, explosions, and infrastructural problems. Results: The data indicated that war situations significantly increased anxiety, negatively impacting mental health, and raising somatic symptom severity. While habituation showed a mild buffering effect on these impacts, resilience did not. Conclusion: This real-world investigation supports TMT's fundamental assumptions about death awareness and its psychological implications. However, even amidst the presence of real, lifethreatening situations, the buffering effects of habituation were surprisingly minimal. This suggests that further exploration of TMT's buffering factors in real-world scenarios is warranted.